Managing non-sewered human waste using thermochemical waste treatment technologies: a review - Beik, Farhad; Williams, Leon; Brown, Tim; Wagland, Stuart T. (MDPI, 2021)
The utilisation of micro-scale thermal treatment technologies for non-sewered applications has been emerging as a prominent route for the safe treatment and disposal of high water content hazardous feedstock. This study provides a comprehensive review of the technological concepts practiced up to date in commercial/pilot and small scales for various types of solid fuels. The respective challenges are critically described and discussed to aid in the selection of promising technology for on-site sanitary applications. Furthermore, the challenges observed with the nominated (pyrolysis) technology are discussed in detail and addressed. This study suggests rapid energy recovery from by-products primarily made up of the highest yield of syngas with a desirable calorific value. The optimum operating ranges are discussed to ensure a reliable thermal conversion of sludge materials considering the application constraints and technology drawbacks. However, further studies are needed to investigate the uncertainties regarding emissions, energy consumption and overall associated costs.
Keywords: sewage sludge; faecal; combustion; gasification; pyrolysis; thermochemical conversion; syngas; bio-oil